Virtualization of Polish E-Consumer Behaviour in Times of Pandemics: Past and Present - Jolanta TARAPATA (Communications of International Proceedings, 2021)
The Internet and modern technology have entered the lives of modern consumers to accompany them from dawn to dusk (and sometimes much longer) every day. More and more daily activities are moving from the real to the virtual world. Hobbying, entertainment, education, shopping, consulting, acquiring knowledge, seeking opinions, making new acquaintances, or keeping in touch with others are all activities that consumers engage in online more often than ever before. Recently, the Covid-19 virus pandemic has had an impact on increased consumer online activity. The aim of the paper is to present the current knowledge on the virtual online behaviour of Polish consumers during the pandemic and to compare it with activity in earlier years based on the analysis of the literature on the subject and secondary sources - research reports. The study assumes that the popularization of Polish consumers' access to the Internet, as well as the period of social isolation caused by the pandemic, has intensified consumers' online activity, especially in their use of the Internet for shopping, cognitive purposes, and interaction and communication with others.
Keywords: Consumer Behavior; Virtualization Of Consumption; Covid-19 Virus Pandemic.